MODELED SHALE AND SANDSTONE BURIAL DIAGENESIS BASED ON THE K-AR SYSTEMATICS OF ILLITE-TYPE FUNDAMENTAL PARTICLES - Clauer N.; Rousset D.; Środoń J. (My University, 2004)
The clay fraction of the sedimentary succession beneath the Mahakam Delta (eastern Kalimantan, Indonesia) consists mainly of mixed-layer illite-smectite, with minor amounts of kaolinite and/or dickite, discrete detrital illite and chlorite. On the near-shore anticline, evolution of this mixed-layer material is characterized by a decrease in expandability with depth. The mechanism of conversion of smectite to illite layers depends on the lithology of the host rocks: it evolves along a solid-state transformation in the shales and a dissolution-precipitation in the sandstones.Illite fundamental particles from two sandstones buried at ∼4000 m in the Tambora field next to the Handil field on the same near-shore anticline yield a mean K-Ar age of 15.7±1.6 Ma (2σ), which is younger than the stratigraphic age but still slightly biased by minute amounts of discrete detrital illite. Recalculated after modeling, which takes into account the occurrence of the discrete detrital illite, this KAr age becomes 14.4±0.7 Ma. The K-Ar values of the fundamental particles from associated buried shales are significantly older, which can be explained by a mixture of (1) a precursor material similar to that presently deposited in the delta of the Mahakam River, and (2) authigenic fundamental particles incorporating Ar with a 40Ar/36Ar ratio above atmospheric value during nucleation and growth on the same detrital precursor.Application of the modeling to the burial evolution of <0.4 µm particles from both the shales and the sandstones of the basin points to a contribution of detrital micaceous material in both lithologies, (1) in the sandstones as a detrital component dissolving progressively and mixed mechanically with the authigenic fundamental particles, and (2) in the shales as a detrital precursor progressively releasing radiogenic 40Ar by burial alteration, and at the same time acting as a support for the fundamental particles for the growth of authigenic fundamental particles that were found to incorporate Ar characterized by an excess of 40Ar.